Effectiveness and Safety of Large Gel Particle Hyaluronic Acid With Lidocaine for Correction of Midface Volume Deficit or Contour Deficiency. Issue 6 (June 2016) - Weiss, Robert A.; Moradi, Amir; Bank, David; Few, Julius; Joseph, John; Dover, Jeffrey; Lin, Xiaoming; Nogueira, Alessandra; Mashburn, Jay
Abstract : BACKGROUND: Aging effects, such as facial flatness, increased tissue laxity, and soft tissue descent and deflation, contribute to midface deficiency. OBJECTIVE: To evaluate whether large gel particle hyaluronic acid with lidocaine (LGP-HAL) is more effective in the treatment of midface deficiencies than no treatment. MATERIALS AND METHODS: Subjects with mild to substantial loss of midface fullness were randomized 3:1 to LGP-HAL (Restylane Lyft; Galderma Laboratories, L.P., Fort Worth, TX) or no treatment. Treatment success was defined as at least 1-grade improvement in Medicis Midface Volume Scale (MMVS) on each side of the face at 8 weeks as assessed by a blinded evaluator. Secondary efficacy end points included MMVS score, global aesthetic improvement, and subject satisfaction. RESULTS: Significantly greater percent of subjects achieved treatment success in the LGP-HAL group compared to no treatment at all time points through Month 12 ( p < .001). One year after initial treatment, 85% of subjects still had a global aesthetic improvement assessed by the treating investigator. Subject satisfaction demonstrated that LGP-HAL improved the aesthetic appearance of the midface. Most reported adverse events (80%) were mild in severity. CONCLUSION: The LGP-HAL treatment is well tolerated and provides significant improvement up to 12 months for the correction of midface deficiencies.